AGENIASP1S CITRICOLA (HYMENOPTERA: ENCYRTIDAE), PARASITOIDE ESPECÍFICO DE PHYLLOCNISTIS CITRELLA (LEPIDOPTERA: GRACILLARIIDAE): INTRODUCCIÓN Y DATOS PRELIMINARES SOBRE SU DESEMPEÑO EN LA ARGENTINA - Diez, P. A.; Fidalgo, P.; Frías, E. (Acta Entomológica Chilena, 2022)
A. citricola was fortuitously introduced in Argentina, probably together with it host. Nevertheless, this species was introduced again in citrus orchards from Perú. A key to sepárate the two species of Ageniaspis known for Argentina and bibliography on life history and use in biological control are provided. Data about the performance of this exotic species are compared with that of native parasitoids.